Business Networks and Innovation in SMEs of a Developing Country (2010)
The impact of business networking on innovation has been analyzed from different perspectives [Granovetter et al. (2000), Callon (2001), Cowan (2004), Powell and Grodal (2005), Cantner and Graf (2006)]. One central issue is whether informal and formal innovation-related links have differential effects on the innovation performance of a firm. This relationship is of particular interest in the case of SMEs, since it can be argued that external links may compensate the limitations imposed by their size and lack of resources. We address the issue empirically, using data for 4,003 SMEs in Colombia. Poisson regression models are used for explaining innovation counts, and Zero-Inflated Poisson models are best suited for firm-level data of SMEs in developing countries, where a large proportion of firms report zero innovations. Results indicate that both formal and informal links are important determinants of the innovation performance of SMEs. Internal capabilities of the firm moderate the rela-tionship between informal network links and innovation outcomes. Given the extent of imitation activities in firms of a developing country, a distinction is made between the analysis of product innovations based on invention and on imitation. In the case of inventions, informal links have a relatively higher importance than formal links, and mediate the relationship between internal capabilities and invention-based innovation counts. Finally, a comparison is made between innovation networking in SMEs and in large firms. Results show divergence on the relative importance of formal and informal links. The results are valuable for innovation policy design.